Performance of Stochastic Targeted Blood Glucose Control Protocol by virtual trials in the Malaysian intensive care unit - Jamaludin U.K.; M. Suhaimi F.; Abdul Razak N.N.; Md Ralib A.; Mat Nor M.B.; Pretty C.G.; Humaidi L. (Elsevier Ireland Ltd, 2023)
Blood; Glucose; Insulin; Intensive care units; Patient treatment; Stochastic control systems; Stochastic models; Blood glucose controls; Blood glucose level; Blood glucose management; Critically-ill patients; Graphical comparison; Hyperglycaemia; Insulin sensitivity; Scale method; Stochastic systems; glucose; insulin; adult; aged; Article; blood glucose monitoring; comorbidity; controlled study; diabetes mellitus; diabetic patient; female; glucose blood level; human; hyperglycemia; insulin blood level; insulin infusion; insulin release; insulin sensitivity; intensive care unit; major clinical study; Malaysia; male; retrospective study; stochastic model; blood; computer simulation; critical illness; diabetes mellitus; diabetic complication; glucose blood level; hyperglycemia; intensive care; Markov chain; middle aged; non insulin dependent diabetes mellitus; reproducibility; Adult; Aged; Blood Glucose; Computer Simulation; Critical Care; Critical Illness; Diabetes Complications; Diabetes Mellitus; Diabetes Mellitus, Type 2; Female; Humans; Hyperglycemia; Intensive Care Units; Malaysia; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Stochastic Processes